Delegating rights protection the rise of bills of rights in the Westminster world - Erdos, David Oliver, 1978- (Oxford : Oxford University Press, 2010)
'Delegating Rights Protection' provides a socially and political grounded analysis of the deliberate political genesis of bills of rights in advanced democratic settings. The book particularly concentrates on exploring bill of rights outcomes in four Westminster democracies: Australia, Canada, New Zealand, and the UK.
Description based on online resource; title from PDF title page (viewed on Sept. 7, 2010).
Includes bibliographical references and index.
Keywords: Civil rights -- Australia; Civil rights -- Canada; Civil rights -- Great Britain; Civil rights -- New Zealand